BIFUNCTIONAL CHIRAL AUXILIARIES .6. ALKYLATIONS OF ENOLATES DERIVED FROM 1,3-DIACYLIMIDAZOLIDINE-2-THIONES AMD 1,3-DIACYLIMIDAZOLIDIN-2-ONES - Davies, S; Evans, G; Mortlock, A (1994)
Sodium and potassium enolates of 1,3-diacylimidazolidin-2-ones undergo clean alkylation reactions with reactive alkyl halides; the latter enolates reacting generally more stereoselectively due, it is proposed, to the lower temperature at which the reactions proceed. The reactions are all stereoregular, with the diastereoisomeric identity of products being established unambiguously by the synthesis of (2S)-3-phenyl-2-methylpropan-1-ol. The sense of asymmetric induction in these reactions is consistent with the intermediacy of chelated syn enolates which the electrophile approaches preferentially from the face exo to the proximate alkyl / aryl group on the five-membered ring. In contrast, 1,3-diacylimidazolidine-2-thiones are unable to act as bifunctional chiral auxiliaries in alkylation reactions due to enolate decomposition. © 1994.